The fall of Hosni Mubarak: Skocpol's structural approach - Price, Clare (Department of Political Studies, 2014)
The recent Arab Spring movement in the Middle East and North Africa has been heralded as a transition to democracy for a region plagued by authoritarian regimes and their durable leaders. This paper seeks to understand why Hosni Mubarak, Egypt's former long-time president, was forced from office during the early months of 2011. Influenced by recent work in political scholarship on the Middle East, the Post-democratisation paradigm, seeks to escape from the democratisation paradigm. Instead of viewing events as indicative of inevitable democratisation in the region, the paper attempts to explain events in terms of Skocpol's structural approach to revolution which can also be used to understand significant social change. In line with the structural approach the paper provides a contextual and narrative history of Egyptian politics, including opposition and protests, as a backdrop to the events between the 25th of January and the 11th of February 2011 which led to Hosni Mubarak leaving office. The paper exhibits structural contradictions in the Mubarak regime, some of which would lead to tension in the elite. Specifically, it highlights tension between the military and the Mubaraks over the matter of Gamal Mubarak's apparent succession of his father. This explains why the military would not use coercive force to help maintain Mubarak's power. It found that the social movement #January25 was successful at maintaining momentum in the face of state repression, including an analysis of the role of social media.